Analisis Komparatif Kinerja Keuangan Sebelum dan Selama Pandemi Covid-19 Pada PT Semen King Stone (Persero) Tbk - Safrizal Safrizal; Annatasya Nur Isnaini (Jurnal Ilmiah Akuntansi Kesatuan, 2023)
The aim of this study is to analyze a comparison between financial performance before and during the Covid-19 pandemic to find out what changes have occurred to PT Semen Baturaja (Persero) Tbk after the incident. This research uses a quantitative descriptive method. The data analyzed is in the form of financial reports for the 2018-2021 period. This data is secondary data obtained by accessing www.idx.co.id and/or visiting the website of PT Semen Baturaja (Persero) Tbk. The results of this study indicate that the financial performance seen from the calculation of the profitability ratio is considered not good because it has not been able to meet industry standards. The value of the profitability ratio has decreased during the Covid-19 pandemic. Meanwhile, the financial performance seen from the liquidity ratio is considered quite good because during the pandemic the company was able to increase the score of this ratio so that it met industry standards, even though at the beginning of the pandemic the company experienced a decrease in the value of the liquidity ratio. There are several studies of financial performance in assessing the performance of a company regarding the issue of comparison of company ratios. But only limited to financial conditions, this research is intended to contribute to the field of environmental health conditions, namely from the point of view of the current Covid 19 pandemic.